The role of resveratrol on rheumatoid arthritis: From bench to bedside - Sheng, Shuyan; Wang, Xinyi; Liu, Xin; Hu, Xinyang; Shao, Yubao; Wang, Gaoyuan; Mao, Deshen; Li, Conghan; Chen, Bangjie; Chen, Xiaoyu (Frontiers in Pharmacology, 2022)
Rheumatoid arthritis (RA) is a systemic autoimmune disease with symmetrical polyarthritis as the main clinical manifestation. Uncontrolled RA will eventually lead to joint deformity and loss of function. At present, the pathogenesis of RA is still under discussion，the treatment of RA is still in the bottleneck stage. Resveratrol has long been regarded as an potential anti-oxidation drug in the treatment of RA. Currently, Resveratrol is considered to have therapeutic effects on RA by activating SIRT1 and its downstream pathways. There is exciting crosstalk between the SIRT1 pathway, NF-κb pathway ,and so on. These pathways, which play an essential role in the development of RA, are linked in unexpected ways under the influence of Resveratrol. Based on recent studies of almost all the pathways that Resveratrol can affect, this review summarized a regulatory chain of core components covering multiple tracks, and list the effects of Resveratrol on immune cells and other subtle controls, which can help clinicians have a new understanding of the known mechanism of resveratrol and use it better.